Effect of Credit Management on the Financial Performance of Deposit Money Banks in Nigeria - Adebayo Abiodun Oluwafemi; Adeusi Stephen Oluwafemi Oluwafemi; Ayorinde Babatunde Femi (Mikailalsys Journal of Mathematics and Statistics, 2026)
This study investigated the effect of credit management on the financial performance of deposit money banks in Nigeria over a 25-year period from 2000 to 2024. Credit management was proxied by the non-performing loan ratio, loan-to-deposit ratio, and capital adequacy ratio, while bank performance was measured using return on equity (ROE). The study used secondary data and employed the Johansen cointegration technique to examine the existence of a long-run relationship among the variables. The results indicate the presence of one cointegrating equation at the 5% significance level, confirming a long-run equilibrium relationship. An error correction model (ECM) was subsequently estimated to capture short-run dynamics and long-run adjustment. The ECM results reveal a statistically significant and correctly signed error correction term, indicating that approximately 1.13% of short-run disequilibrium is corrected annually. Furthermore, the findings show that credit risk management variables exert negative but statistically insignificant effects on ROE. Despite the individual insignificance of the explanatory variables, the overall model is statistically significant and free from serial autocorrelation. The study concludes that credit management indicators exert a weak influence on the profitability of deposit money banks in Nigeria. These findings contribute to banking and financial performance literature by providing empirical evidence on the limited explanatory role of selected credit management indicators in determining profitability and offer practical implications for bank managers and regulators in strengthening credit risk assessment, loan portfolio quality, and capital management practices.